A virtual reality system for the determination of critical machining-process parameters. (4th June 2010) - Petousis, Markos A.; Bilalis, Nickolas; Sapidis, Nickolas S.
Recently, virtual reality systems have been presented for simulation of machining processes, aiming at the determination of specific machining parameters, such as the required fixtures and the machining environment, the cutting tool dynamics, the chip shape and volume, and the shape of the cutting tool. This study proposes a methodology for the development of a virtual environment for three axis milling process simulation. The technological and research challenges involved in this methodology are described. The operation of a new system developed by the authors for machining-process simulation in a virtual environment is presented. This system integrates a virtual reality environment with computational and graphical models for the simulation of three axis milling processes. A computational model has been developed for the visualisation of the milling process in the virtual environment and graphical model has been developed for the calculation of quantitative data related to surface roughness of machined surfaces.